Exploring Husband Involvement in Antenatal Classes : A Mix-Method Approach on Demographic, Structural, and Psychological Dimensions - Tungga Dewi, Christin Hiyana; Rahfiluddin, Mohammad Zen; Sriatmi, Ayun; Agushybana, Farid (YCAB Publisher, 2025)
Background: The involvement of husbands in the health of pregnant women is very important; adequate knowledge supports their role as good companions. Antenatal classes aims to reduce the knowledge gap between couples by involving husbands. However, the participation of husbands remains low. Objective: The study aims to analyze the correlation between the demographic, structural and psychological dimensions of husband's involvement and to identify the different reasons for low husband's involvement in antenatal classes. Methods: This is a cross-sectional study using a mixed methods approach. The study population consisted of the husbands of pregnant women who attended antenatal classes during the period December 2021 to May 2022 (6 months), totaling of 254 people. The sample siza was determined using the sample size formula for a known population, resulting in 168 people selected through a proportional sampling technique. Data collection was conducted through interview. Bivariate data analysis was performed using Chi-Square test, and multivariate analysis was conducted using Multiple Logistic Regression test. Qualitative data collected through in-depth interview based on interview guidelines with 5 (five) husbands as main informants, 3 (three) pregnant women and 1 (one) health worker (midwife) as triangulation informants. The data were analyzed using thematic analysis approach. Results: Partially, education and occupation variables were significantly associated with husband's participation in antenatal class (p<0.05). Simultaneously, education and perceived barriers were shown to jointly influence husband's involvement in antenatal class (p<0.05). The odds of husband's participation in antenatal class increase by 5.6 times as education increases. Additionally, the odds of involvement would be 3.266 times greater if there were no perceived barriers. Conclution: The use of educational technology as a medium of communication and information is an alternative to reduce perceived barriers related to time and work constraints.